2022
DOI: 10.1097/scs.0000000000008682
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Factors Affecting Postoperative Drainage After Comprehensive Rhinoplasty

Abstract: This study aimed to explore and analyze the factors influencing the drainage volume after comprehensive rhinoplasty. The clinical data of 102 patients who underwent comprehensive rhinoplasty at Shanghai Ninth People’s Hospital affiliated to Shanghai Jiao Tong University School of Medicine from August 2019 to August 2021 were retrospectively analyzed. The effects of age, sex, body mass index, whether an osteotomy was performed, and whether a nasal septum flap was obtained on the indwelling time of the drainage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Our findings were consistent with other studies, which also identified a significant positive correlation between age and both the time of drainage and total drainage volume. These results highlight the potential impact of age on postoperative recovery and emphasize the need for careful monitoring and management in elderly patients undergoing surgery ( 9 , 10 ). Lee et al ( 11 ) also reported that advanced age was an independent risk factor with increased time of drainage.…”
Section: Discussionmentioning
confidence: 69%
“…Our findings were consistent with other studies, which also identified a significant positive correlation between age and both the time of drainage and total drainage volume. These results highlight the potential impact of age on postoperative recovery and emphasize the need for careful monitoring and management in elderly patients undergoing surgery ( 9 , 10 ). Lee et al ( 11 ) also reported that advanced age was an independent risk factor with increased time of drainage.…”
Section: Discussionmentioning
confidence: 69%